Anti-CTLA4 Monoclonal Antibody Ipilimumab in the Treatment of Metastatic Melanoma: Recent Findings - Lens, Marko; Ferrucci, Pier F.; Testori, Alessandro (Recent Patents on Anti-Cancer Drug Discovery, 2008)
Use of monoclonal anti-CTLA4 antibodies represents a new promising strategy to block the activation of immunosuppressive CTLA-4 and thus induce tumour regression. This review is mainly focused on the report of existing data on the clinical use of Ipilimumab (formerly MDX-010) in the treatment of metastatic melanoma. Several phase I and II trials have been conducted to evaluate safety and efficacy of this form of immunotherapy either alone or in combination with vaccines or chemotherapy in patients with stage III or stage IV melanoma. Results from these studies are presented, patented and discussed. The mechanism of ipilimumab action may take time to induce an anti-tumour immune response and thus it is recommended that ipilimumab therapy should be carried out for at least 12 weeks, even in the presence of early progressive disease. Objective response of around 15% has been reported in patients treated with ipilimumab. However, ipilimumab-mediated objective response and stable disease tend to be durable. The therapy with ipilimumab is associated with different side effects classified as immune-related adverse events (IRAEs). The most common IRAEs are enterocolitis and dermatitis. Majority of IRAEs disappear with the discontinuation of ipilimumab anti-CTLA-4 therapy. Several phase II/III trials are ongoing to evaluate ipilimumab alone or in combination with other therapeutic modalities. Results from these trials are awaited.
Keywords: ipilimumab